THE ROLE OF EVENT ATTENDEES’ KNOWLEDGE, ENTHUSIASMS, AND ACTIVENESS ON COMMUNITY INVOLVEMENT - Christina Rahardja Honantha (Manajemen dan Bisnis, 2013)
Today, events are central to our culture as perhaps never before. Increases in leisure time anddiscretionary spending have led to a proliferation of public events, celebrations andentertainment. The event marketing manager must then examine the objectives of these majorplayers – what each of them expects to gain from the event, and what forces acting on them arelikely to affect their response to the event. This study to examine the relationships among eventattendees' knowledge of an event sponsor's products and activeness and enthusiasm related to thearea of the event for a sponsor’s community involvement. This approach assumes that marketers,by adopting a consumer focus, respond only to the expressed needs of event visitors. In reality,sound marketing research can unveil the latent needs of consumers that only innovative eventscan satisfy. Event marketing is defined as the "practice of promoting the interests of anorganization and its brands by associating the organization with a specific activity" (Shimp,1993; Van Heerden, 2001). Data with 200 respondents are analyzed with multiple linierregressions, and hypotheses are also tested for significant influences. The result shows that eventattendees' knowledge of the sponsor, enthusiasm, and activeness positively influence their desirethat a sponsor be involved with the community, which can make the event special, and contributeto its imagery and branding.Saat ini event menjadi tema sentral dalam budaya manusia. Peningkatan waktu luang danpengeluaran telah mendorong munculnya berbagai macam event publik, perayaan dan hiburan.Manajer event marketing harus mempelajari tujuan dari berbagai macam pemeran dalamperayaan tersebut, apa yang diharapkan dari suatu peristiwa serta hal apa yang mendorongkonsumen menyukai suatu event. Penelitian ini memeriksa hubungan antara pengetahuan pesertaevent akan event yang didanai produk sponsor, dan tingkat keaktifan serta antusiasme terkaitdengan keterlibatan komunitas tertentu. Pendekatan ini memiliki asumsi bahwa pemasar akamerespon kebutuhan yang tampak dari pengunjung event. Dalam kenyataan, dengan risetpemasaran yang kuat maka dapat ditemukan kebutuhan tersembunyi dari konsumen. Eventmarketing didefinisikan sebagai kegiatan praktik promosi kepentingan organisasi dan merekdikaitkan dengan event/peristiwa tertentu (Shimp, 1993; Van Heerden, 2001). Data diperolehdari 200 responden dan diolah dengan regresi linear. Hasil penelitian menunjukan pengetahuanpengunjung akan sponsor, antusiasme, dan tingkat keaktifan berpengaruh positif terhadapkeinginan agar sponsor terlibat dengan komunitas tertentu, sehingga event dapat menjadi lebihmenarik dan berpengaruh pada branding dan citra merek.